Relationship of work motivation with nurse performance in Installation Room of Islamic Hospital - Priyantini, Diah; Ayatulloh, Daviq (Palembang MediRose Publisher, 2023)
Background: Work motivation is often the cause of the reduced performance of nurses, it is related to the lack of internal and external motivation in the work. Objective: This study aimed to analyze the relationship between work motivation to nurse performance in the installation room of an Islamic hospital. Methods: The design of this study uses cross-sectional methods. The sampling method used is purposive sampling. Samples taken by 35 respondents are nurses who work in the Inpatient Room of Sakinah Islamic Hospital, Mojokerto, East Java. Research data was taken using motivation sources inventory and a nurse’s work functioning questionnaire that was validated with an r count of 0.786-0.912 and reliable (Cronbach alfa = 0.876). After the tabulated data were analyzed using the Spearman Rho test with a significance level of 0.05. Results: The results showed the motivation of nurses working in the high category (65.7%) and nursing performance showed in the excellent category (57.1%). While the results obtained from the statistical tests showed a correlation between nursing motivation and the performance of nurses with a correlation value of 0.728 with p < 0.001. Conclusions: Seeing these results it is necessary to coach the head office and nurses by providing training to improve motivation and performance so nurses can lead to good service and a good image for the hospital in the community.